Mobile communications data services marketing - Stanislav Marušić (Tržište, 2006)
Increasing revenue per user is very important for mobile operators because of shrinking growth from mobile voice services on a number of markets. At the same time, a more powerful platform enabling advanced mobile data services has emerged. Therefore, mobile data services offer great possibilities to operators in the future. Marketing plays the key role in offering new and existing data services. Experiences in launching various services, primarily a comparison of Japanese and other experiences, shows that different strategies and marketing mix employed in launching data services can lead to different business results in this area. The needs and preferences of Croatian mobile users are explored in this paper, especially in the following areas: the most used and potentially most interesting data services, a preferred way of paying for these services, the importance of transaction security in mobile payments and a comparison of the use of and interest in such services by users with more advanced mobile terminals and those with older mobile phones. Results imply that a strong and attractive presence of these services in the media is crucial to success. It is also important to communicate clearly the benefits of these services, along with lower prices (or promotional periods) as well as easy activation and use. Last but not least: the existence of attractive content and applications (where fair arrangements among all providers of these services is the main prerequisite) is essential for a faster adoption and use of these services.